Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
Carta relacionada a asuntos politicos.
Keywords: Barceló, Antonio R., 1868-1938; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Montgomery Reily, Emmet, 1866-1954; Tous Soto, José, 1874-1933